Actuator fault estimation for two-stage chemical reactor system based on delta operator approach. (November 2021) - Wu, Yu; Du, Dongsheng; Liu, Bei; Mao, Zehui
Abstract: Based on the delta operator approach, a new method of actuator fault estimation for a two-stage chemical reactor system is presented with time-delay and outside disturbances. Firstly, a nonlinear delta operator mathematical model is established to describe the two-stage chemical reactor systems by using the mechanism analysis method. In order to estimate the actuator fault, the proportional–integral observer (PIO) is employed as the state estimator. Meanwhile, a novel delta operator-based actuator fault estimation algorithm is proposed. Then, by means of the Lyapunov–Krasovskii functional technique, sufficient conditions are derived to guarantee that the error system is asymptotically stable with a predefined H ∞ performance index. Next, the desired PIO can be designed. Finally, simulation results are given to illustrate the effectiveness of the proposed methods. Highlights: A novel proportional and integral fault estimation algorithm is firstly proposed. This method connects continuous-time systems and discrete-time systems. A practical simulation example is given to verify the method. The system model in this paper is more universal and practical.